Decrease of Pericytes is Associated With Liver Disease Caused by Ligature‐Induced Periodontitis in Rats. Issue 2 (1st February 2017) - Vasconcelos, Daniel Fernando Pereira; Pereira da Silva, Felipe Rodolfo; Pinto, Moara e Silva Conceição; Santana, Lucas de Araújo Bastos; Souza, Ingrid Grazielle; Miranda de Souza, Luan Kelves; Oliveira, Natássia Cristina Martins; Ventura, Claudio Angelo; Novaes, Pedro Duarte; Barbosa, André Luiz dos Reis; Medeiros, Jand‐Venes Rolim; Mikolasevic, Ivana; et al.
Abstract : Background: Damage caused by periodontitis not only affects periodontal tissues, but also increases the severity of various illnesses such as rheumatoid arthritis, diabetes, and liver diseases. The aim of this study is to investigate the association between induced periodontitis and damage caused through its systemic effects on the liver. Methods: Twenty rats were divided into two groups: control and periodontitis. The following parameters were evaluated: gingival bleeding index (GBI), probing depth (PD), myeloperoxidase (MPO) activity, alveolar bone loss (ABL) for periodontal tissues; histopathologic examination of gingival and liver tissues; immunohistochemistry to cells positive for neural/glial antigen 2 (NG2) expressed in hepatic pericytes, glutathione (GSH), and malondialdehyde (MDA) concentrations in liver; and serum levels of alanine aminotransferase and aspartate aminotransferase. Results: GBI, PD, MPO, ABL, and histopathologic examinations demonstrated the development of periodontitis. There was a significant increase in microvesicular steatosis accompanied by a marked reduction in NG2+ pericytes in the periodontitis group compared with the control group. The periodontitis group had significantly lower GSH and higher MDA concentration in the liver compared with the control group. Conclusions: The present study results link the systemic effects of induced periodontitis with changes in hepatic tissues such as microvesicular steatosis, likely caused by an increase in oxidative stress and lipid peroxidation. The findings from the present study implicate an association between a decrease of pericytes and liver disease caused by ligature‐induced periodontitis in rats.